Balanced Nutrition in School-Age Children - Fahmi Fuadah; Gurdani Yogusutanti; Tri Ardayani; Neti Sitorus; Linda Hotmaida (Asosiasi Profesi Multimedia Indonesia, 2023)
This community service aims to implement community nutrition intervention activities in overcoming nutritional problems in Pamengkang Village, Kramatwatu District, Serang Regency, Banten Province. This community service activity was carried out by onsite / direct visit to Pamengkang Kramatwatu District, Serang Regency, Banten Province through a process of planning, implementation and evaluation on February 1, 2023. Followed by 30 health cadres, 30 mothers who have babies, and 30 elementary school children consisting of grades 3, 4, 5. Data collection techniques using documentation. The outputs of this activity are in the form of a certificate of Community Service, a report on the Activity